Application of non-invasive neuromodulation in children with neurodevelopmental disorders to improve their sleep quality and constipation - Aníbal Báez-Suárez; Iraya Padrón-Rodríguez; Elizabeth Castellano-Moreno; Erica González-González; María P. Quintana-Montesdeoca; Raquel Irina Medina-Ramirez (BMC, 2023)
Abstract Background Children with neurodevelopmental disorders have a very wide clinical variability. A common prevalent factor is problems with stool and sleep quality. Currently, there are multiple studies related to their evaluation, but not so much related to a specific intervention. The aim was to evaluate the effectiveness and safety of the application of non-invasive neuromodulation as a treatment in children with neurodevelopmental disorders to improve constipation and quality of sleep. Methods A total of 23 minors aged between 2 and 16 were included in this cross-sectional study. All participants were applied the microcurrent device for 60 min, 3 times per week for a total of 4 weeks. The technique was based on non-invasive neuromodulation using a surface-applied microcurrent electrostimulation device that administers an external, imperceptible, pulsed electrical stimulation. It is applied to the extremities, in a coordinated manner, using gloves and anklets connected with electrodes to a control console. Sleep latency and microarousals were evaluated through a sleep diary. To assess the evolution and type of defecation, the adapted and validated version in Spanish of the Bristol Stool Form Scale was used. Results No adverse events occurred during the study and no incidences were registered. Clinically relevant improvements were registered in defecation frequency and type as well as in sleep related parameters. An increase in the hours of sleep was registered, from 7,35 (0,83) to 9,09 (1,35), and sleep interruptions decreased from 3,83 (1,95) to 1,17 (1,11), (p < .001). Conclusion Microcurrents can be used as an effective and safe treatment to improve quality of sleep and constipation in children with neurodevelopmental disorders. More studies are needed in order to obtain statistically significant results. Trial Registration ClinicalTrials.gov ID: NCT05265702. First registration 03/03/2022 Protocol https://clinicaltrials.gov/ct2/show/NCT05265702?term=baez+suarez&draw=2&rank=4